Exploring Language Politeness Strategy Among Indonesian Moslem Preachers - Wulansari, Atsani; Mazid, Sukron (UPA Bahasa Universitas Tidar And HISKI Kedu, 2025)
Preachers utilize language to deliver their da’wah and communicate their important messages to the audience. As such, the use of politeness strategies is essential to minimize face-threatening acts (FTAs) and ensure that the message is communicated in a respectful and persuasive manner. Therefore, this study aims to analyze the politeness strategies used by Male Indonesia Preachers. This research applies qualitative research method with discourse analysis. Four specific YouTube channels were chosen as the sources for the data. The data for this research consists of da’wah utterances from four different male preachers featured on YouTube. To collect the data, the researchers followed several steps: selecting the preachers, watching the videos on their YouTube channels, and transcribing the utterances from the videos. Brown and Levinson's theory of politeness strategies is applied to analyze and interpret the data. The politeness strategies employed by the four preachers in Indonesia include bald-on-record, positive politeness, and negative politeness. The findings highlight that Indonesian preachers predominantly use bald-on-record and positive politeness strategies, effectively balancing directness with respect for their audience.